An opportunity for a different Peru : prosperous, equitable, and governable - Giugale, Marcelo; Fretes Cibils, Vicente, 1956-; Newman, John L., 1955- (World Bank e-Library., 2007)
For the first time in the republican history of Peru, the presidential transition takes place in democracy, social peace, fast economic growth and favorable world markets. In other words, there has never been a better chance to build a different Peru - a richer country, more equal and governable. There are multiple ways to achieve that goal. New reforms must stem from a widespread and participatory debate, one of a common vision conceived for and by Peruvians. This book aims at making a technical and independent contribution to such debate; it summarizes the knowledge available about the challenges to be faced by the new administration.